Range expansion, density and conservation of the Araucaria Tit-spinetail Leptasthenura setaria (Furnariidae) in Argentina : The role of araucaria Araucaria angustifolia (Araucariaceae) plantations - Cabanne, Gustavo Sebastián (2007)
Fil: Cabanne, Gustavo Sebastián. Departamento de Genética e Biologia Evolutiva; Instituto de Biociências; Universidade de SÆo Paulo; SP; Brazil